21st Century Skill Acquisition for Career Readiness of Business Education Undergraduates of Public Universities in Anambra State - Faith; Chinwe; Cornelius (Journal of Research in Industrial Technology and Educational Studies, 2026)
This study examined the 21st century skill acquisition and career readiness of business education undergraduates in public universities in Anambra State. Two research questions guided the study. The study adopted a descriptive survey design. The population comprised 120 final year business education undergraduates and data were collected using a structured questionnaire developed by the researcher. The reliability coefficients were 0.76 for Cluster 1 and 0.84 for Cluster 2, yielding an overall reliability index of 0.80. Data were analyzed using mean and standard deviation. Findings revealed that digital literacy skills and communication skills significantly enhance career readiness. The study concludes that acquisition of 21st century skills is crucial for equipping undergraduates with the competencies required to meet workplace demands, adapt to technological changes and achieve career success. It is recommended that business education programmes integrate more digital literacy training, strengthen communication-oriented learning activities and promote creativity and innovation through practical-based instruction.